2009
DOI: 10.1080/01904160903007893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Supply on the Root Morphology of Corn and Velvetleaf

Abstract: Root morphology will affect interplant competition for soil nutrients. Research was conducted to assess fine root fraction, mean root radius, specific root length, root length density, and nitrogen (N) uptake per unit fine root biomass of corn and velvetleaf over time and in response to nitrogen supply. Pots containing either corn or velvetleaf were embedded in the ground and received one of three N treatments. Plants were destructively sampled on 10 dates during each of two years and root subsamples analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…neighbouring species) through changing the belowground rooting strategy and foraging ability (Fransen et al, 1998;Pergitzer et al, 2002;Messier et al, 2009). Plants may adopt either extensification strategies by increasing investment of carbon into fine roots or intensification strategies by altering absorption efficiency through morphological plasticity, or both (Ostonen et al, 2007a;Bonifas and Lindquist, 2009). Morphological plasticity is one of the most important responses to environmental changes (Fitter, 1987;Lohmus et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…neighbouring species) through changing the belowground rooting strategy and foraging ability (Fransen et al, 1998;Pergitzer et al, 2002;Messier et al, 2009). Plants may adopt either extensification strategies by increasing investment of carbon into fine roots or intensification strategies by altering absorption efficiency through morphological plasticity, or both (Ostonen et al, 2007a;Bonifas and Lindquist, 2009). Morphological plasticity is one of the most important responses to environmental changes (Fitter, 1987;Lohmus et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…According to Berntson et al (1995), Lemaire et al (1996), and Bonifas and Lindquist (2009), there would be three ways for crops to improve their N uptake: they can increase the amount of biomass they allocate to roots, modify their root morphological characteristics, or increase the N uptake efficiency of the root absorbing surface. The latter aspect was not investigated here, and was assumed to be similar among the three species.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that even though sweet pearl millet and sweet sorghum allocated less C to their root system than corn (Table 3), they produced longer root systems (Table 4), which likely increased their competitiveness for nutrients. Moreover, Bonifas and Lindquist (2009) observed that a smaller allocation of resources to roots along with a high SRL may allow for greater investment of resources to the aboveground biomass. This could explain the high aboveground DM yield of sweet pearl millet and sweet sorghum observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The plants that get unlimited water from soil will tend to increase the volume of roots, which will affect the root dry weight [20]. The volume of root was positively correlated with the length of lateral roots and tap root [21]. The surface area of roots of growing medium was related to the surface area of absorption of nutrients.…”
Section: Proportion Of Medium With Fertilizermentioning
confidence: 99%